ANALISIS KESALAHAN KONSEPTUAL DAN PROSEDURAL DALAM MENYELESAIKAN SOAL SPLDP PADA PESERTA DIDIK - Radiatul Adawiah; Muhammad Rahul (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
In learning mathematics of the subject sometimes makes mistakes on working the questions. This can occur due to the subject not understanding the material being taught, not being thorough, not remembering concepts, and mistakes in applying formulas resulting in errors. The purpose of this research is to find out conceptual and procedural errors in solving SPLDV questions for Class X AKL students 1 at the SMK Negeri 1 Kotabaru. This research is a qualitative research with a descriptive approach. The techniques of data collection through the provision of tests and interviews. The research subjects consisted of high-ability subjects, moderate-ability subjects, and low-ability subjects. The results showed that the conceptual errors occurred in students with high capabel, medium and low abilities, namely the indicators of mistake in classifying objects of mathematical based on their properties. Meanwhile, the procedural errors only occur in students with moderate and low abilities, namely the indicators of irregularity by the steps of solving math problems, errors in substituting values into variables, errors in calculations and errors due to not continuing with the solving steps. Keywords: Conceptual Error, Procedural Error.